Pengawasan Yuridis dalam Rangka Mewujudkan Sistem Penyelenggaraan Negara yang Konstitusional - Tanto Lailam (Universitas Bandar Lampung (UBL), 2011)
Juridical control in order to realizirrg constilutional gorerhmehtal system, Juridical control by cohslitution court is juridical control form to prolecling indonesia people eokstitutional right,jutidical conttol to good democracy prccess (president and vice- president electioh, legislative election) also local election, juridical contrcl aboul state organ dispute, and Juridical control of president and vice presidenl of impeachment process. Juridical control functiok by cohstitution courl gtves opportunity lor cohstitulional govenmenld I system based on constitution. Juridical control by Juslice Cont about judicial reviev in this case Juslice Courl as lhe legitb&te inlerpreter ofthe ldw andjuslice, and administr.tlioh coultjuridical conlrcl isjuridical co lrol institution thal has authority to evaluates administration decision oppose against regulation and general basisso fgood, clean, strong government